Association between personality traits and the enjoyment of pimple-popping videos - Arved Seibel; Albert Wabnegger; Anne Schienle (Discover Psychology)
Abstract Background Watching pimple-popping videos has become very popular, particularly on social media. However, the psychological mechanisms behind this novel and puzzling phenomenon remain largely unexplored. Two studies were conducted on this topic. A first study explored the validity of the Pimple Popping Enjoyment Scale (PPES) in terms of predicting viewing behavior during exposure to pimple-popping videos. A second study investigated the association between the PPES and other personality scales. Method In Study 1, 104 participants (mean age = 26 years, 64% female) completed the PPES and watched pimple-popping videos with the option to skip forward and backward during viewing. In Study 2, 501 participants (mean age = 25 years, 79% female) answered the PPES and additional personality scales (e.g., benign masochism (BM), morbid curiosity (MC)). Results Higher scores on the PPES were linked to fewer instances of skipping forward while watching pimple-popping videos, indicating reduced visual avoidance. Hierarchical regression analyses revealed that MC and BM were positively associated with PPES scores. Conclusions The present findings help to understand a social media trend: why people watch and enjoy pimple-popping videos. This behavior is likely motivated by an interest in danger and potential death (MC) and the enjoyment derived from discomfort in non-threatening, controlled situations (BM).